Ti/β-TCP composite porous scaffolds fabricated by direct ink writing. Issue 1 (31st December 2023) - Zhao, Guangbin; Zhang, Qingxian; Qu, Xiaoli; Wu, Yanlong; Chen, Xu; Wang, Yaning; Tian, Hang; Liu, Yaxiong; Li, Zhikang; Lu, Bingheng
ABSTRACT: A Ti/β-TCP composite porous scaffold with a hierarchical pore structure composed of 3D printed interconnected macroscopic pores and sintered microscopic pores was prepared by direct ink writing (DIW) 3D printing technology. This method can control the extrusion of composite ink at room temperature and produce a 3D scaffold using layer-by-layer deposition. We studied the effects of the β-TCP powder particle size, β-TCP/Ti powder ratio and solid loading on the rheological properties of the ink and optimised the DIW printing process parameters. After sintering, the compressive strength and elastic modulus of the composite scaffold reached 45 MPa and 1 GPa, which is close to the strength of human cancellous bone. The cell culture experiment confirmed that the composite scaffold had better biological properties than the pure titanium scaffold. The composite scaffold has satisfactory mechanical and biological properties, meeting the requirements for orthopaedic implants.